Blood Transfusions in Dogs and Cats Receiving Hemodialysis: 230 Cases (June 1997–September 2012). (15th February 2017) - Langston, C.; Cook, A.; Eatroff, A.; Mitelberg, E.; Chalhoub, S.
Abstract : Background: Multiple factors exist that contribute to anemia in dogs and cats receiving hemodialysis, can necessitate transfusion. Objectives: To describe blood product usage in dogs and cats with acute and chronic kidney disease that were treated with intermittent hemodialysis to determine risk factors associated with the requirement for blood product transfusion. Animals: 83 cats and 147 dogs undergoing renal replacement therapy at the Animal Medical Center for acute or chronic kidney disease. Methods: Retrospective medical record review of all dogs and cats receiving renal replacement therapy for kidney disease, from June 1997 through September 2012. Results: Blood products (whole blood, packed RBCs, or stromal‐free hemoglobin) were administered to 87% of cats and 32% of dogs. The number of dialysis treatments was associated with the requirement for transfusion in cats (adjusted OR 2.21, 95% CI 1.13, 4.32), but not in dogs (adjusted OR 0.98, 95% CI 0.95, 1.03). Administration of a blood product was associated with a higher likelihood of death in dogs (OR 3.198, 95% CI 1.352, 7.565; P = .0098), but not in cats (OR 1.527, 95% CI 0.5404, 4.317, P = .2). Conclusions and Clinical Importance: Veterinary hospitals with a hemodialysis unit should have reliable and rapid access to safe blood products in order to meet the needs of dogs and cats receiving dialysis.